Issues of environmental safety of wastewater treatment facilities in Ukraine and examples of solutions based on cities in Ukraine - Linenko, Yevhen (National Technical University "Kharkiv Polytechnic Institute", 2025)
Modern wastewater treatment facilities are often not equipped to effectively remove emerging pollutants such as microplastics, pharmaceutical residues, and other chemical compounds.
Keywords: wastewater treatment; environmental safety; emerging pollutants; industrial pollution; infrastructure modernization